Analisis persepsi generasi Z terhadap produk bank Syariah kota Bengkulu - Vemy Dian Fajri; Dhea Azelia Oktaviani; Uswatun Hasanah (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
in this study stems from the low level of understanding and participation of Generation Z towards Islamic banking products, despite their enormous potential as future customers. Many young people still consider Islamic banking products to be not much different from conventional banks, and some do not even understand basic principles such as the prohibition of usury, fairness, and profit-sharing systems. The low level of Islamic financial literacy among Generation Z results in perceptions ranging from neutral attitudes to a lack of trust in the effectiveness of Islamic banking products in meeting modern financial needs. The purpose of this study is to understand in depth how Generation Z perceives Islamic banking products and the factors that influence these perceptions, such as religious values, financial knowledge, personal experience, and the influence of the social environment. This study uses a qualitative research type with a descriptive method. Data collection techniques are carried out through in-depth interviews and observations of a number of informants from Generation Z in Bengkulu City. The data obtained were then analyzed through data reduction, data presentation, and drawing conclusions to find emerging patterns of perception. The results showed that the majority of Generation Z had a positive perception of the basic principles of Islamic banking, but still had doubts about product innovation and the ease of digital services. Religiosity and Islamic financial literacy factors proved to be the main determinants in shaping Generation Z's positive perception of Islamic banking.